The Degree of Creativty Management and its Relation with the Management Performance for the Government School Principals in the Northern West Bank Directorates form the Teachers Perspeetives - Sana Raji Ahmad Al-Sowadeh (My University, 2016)
The aim of this study is custom management innovation and its relationship to performance management to the principals in the West Bank from the perspective of teachers, as well as this study came to show the role of the Director in the management of innovation and its relation to management performance has from the viewpoint of teachers and parameters for different variables (age, sex, qualifications, experience). To achieve the goal of the study sample consisted of (322) teacher and mentor equivalent (84%) Almost the total number of teachers and parameters, and the number of persons if completed questionnaire (58). The researcher was used in this study is descriptive, with reference to previous literature on the subject to clarify the theoretical background for the study. It is designed to identify targeted data collection on the subject, then it was a statistical data analysis and processing to extract and compare the results. The study questionnaire came (51) distributed to more than one axis, this is in addition to the structural questions of the study to identify the level of management of innovation and its relation to management performance with principals in the provinces of North West from teachers ' perspective, in the light of the theoretical literature on principal and managing for creativity. The study has reached the following conclusions: 1. The role of the principal in the Government school in the northern West Bank in the management of creativity was great for an average 3, 78 and 77 percent. 2. The results also showed creativity management arrangement wherein the area of authenticity in ranked higher arithmetic reached 3.98 79.6%. While his field of fluency on 3, 9 78.0% and allergy problems on arithmetic mean 3, 82 which 76.4% while maintaining attention came in last 3, 78 75.7%. 3. The lack of statistically significant differences at the level of significance (α = 0.05) in the management of creativity and its relationship to performance management to the principals in the provinces of North West from the teachers ' point of view, due to variables (age, sex, qualifications, experience). The researcher concluded after discussing results and compare them with previous studies into more of a recommendation: 1. You must give the principal space required by the Ministry of education to develop creativity can level teachers and students. 2. The need to provide logistical and material support for the headmaster to could implement his plans towards creativity and application of these plans on the ground. 3. The school principal to explain to school staff objectives and future plans for the active participation of teachers could find creative ideas to implement these plans. 4. The principal always work to find renewed structures and systems can manage innovation effectively and efficiently

هدفت الدراسة إلى التعرف على مستوى إدارة الإبداع وعلاقته بالأداء الإداري لدى مديري المدارس الحكومية في محافظات شمال الضفة الغربية من وجهة نظر المعلمين والمعلمات، كذلك جاءت هذه الدراسة لتبين دور المدير في إدارة الإبداع وعلاقته بالأداء الاداري لديه من وجهة نظر المعلمين والمعلمات باختلاف المتغيرات (العمر، الجنس، المؤهل العلمي، سنوات الخبرة). ولتحقيق الهدف من الدراسة أجريت على عينة تمثلت في (322) معلما و معلمة , أي ما يعادل (84,7%) من المجموع الكلي لعدد المعلمين و المعلمات، وكان عدد الأشخاص الذين لم يستكملوا الاستبانة (58) شخصاً. إستخدمت الباحثة في الدراسة المنهج الوصفي،.كذلك تم تصميم استبانة تكونت من (51) فقرة موزعة على محورين, وقد تم تحليل البيانات بواسطة إختبار الإنحدار الخطي المتعدد وقد توصلت الدراسة الى النتائج التالية: بعد تحليل البيانات بواسطة إختبار الإنحدار الخطي المتعدد حيث تبين أن هناك نموذجين فقط قد أثرا في مستوى الأداء الإداري لدى مديري المدارس , النموذج الأول كان للإبداع الإداري , والنموذج الثاني كان للإبداع الإداري مع المؤهل العلمي. وقد تبين أن دور مدير المدرسة في المدارس الحكومية شمال الضفة في إدارة الإبداع كان مرتفعاً بمتوسط حسابي بلغ 3,87 و بنسبة 77،4%. كما أظهرت النتائج في ترتيب مجالات إدارة الإبداع حيث جاء مجال الأصالة في المرتبة الاولى بأعلى متوسط حسابي بلغ 3,98 بنسبة %79.6. بينما حصل مجال الطلاقة على 3,9 بنسبة %78.0 ومجال الحساسية بالمشكلات على متوسط حسابي 3,82 أي بنسبة %76.4 في حين جاء الاحتفاظ بالانتباه بالمرتبة الاخيرة 3,78 بنسبة %75.. وكذلك اتضح عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (α=0.05) في مستوى إدارة الإبداع وعلاقته بالأداء الإداري تعزى إلى متغيرات(العمر، الجنس، الخبرة), بينما كان هناك فروق ذات دلالة إحصائية تعزى لمتغير المؤهل العلمي . وقد خلصت الباحثة بعد مناقشة النتائج بالتوصيات التالية: 1. إعطاء مدير المدرسة المساحة المطلوبة من قبل وزارة التربية و التعليم وذلك ليستطيع تطوير الإبداع على مستوى العملية التعليمية ككل . 2. ضرورة توفير الدعم اللوجستي و المادي لمدير المدرسة ليستطيع تنفيذ خططه نحو إدارة الإبداع و تطبيق هذه الخطط على أرض الواقع. 3. التركيز على المدير صاحب الرؤية التربوية المبدعة و المؤهلات التي يتصف بها القائد التربوي المبدع، عند اختيار مديري المدارس من قبل الجهات صاحبة الإختصاص وإخضاع المديرين الجدد إلى مراحل تعيين مقيمه ومدروسه . 4. الإهتمام بمعيار المؤهل العلمي كأحد المعايير الأساسية عند تقييم المدير وليس الأقدمية مثلا كما هو جاري حاليا في نظام وزارة التربية التعليم العالي. 5. يجب مشاركة المديرين في المؤتمرات و الندوات وورش العمل، وذلك لنقل رؤيتهم الإبداعية للغير واكتساب خبرات أخرى , وإجراء المزيد من البحوث و الدراسات التطبيقية التطويرية لمستوى أدائهم.
درجة إدارة الإبداع وعلاقتها بالأداء الإداري لدى مديري المدارس الحكومية في محافظات شمال الضفة الغربية من وجهة نظر المعلمين والمعلمات